2019
DOI: 10.1101/854885
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Melanoma-secreted Amyloid Beta Suppresses Neuroinflammation and Promotes Brain Metastasis

Abstract: 26Brain metastasis is a significant cause of morbidity and mortality in multiple cancer 27 types and represents an unmet clinical need. The mechanisms that mediate metastatic 28 cancer growth in the brain parenchyma are largely unknown. Melanoma, which has the 29 highest rate of brain metastasis among common cancer types, is an ideal model to 30 study how cancer cells adapt to the brain parenchyma. We performed unbiased 31 proteomics analysis of melanoma short-term cultures, a novel model for the study of 32 b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 78 publications
1
14
0
Order By: Relevance
“…Consistently, we observed that melanoma cells treated with BACE inhibitor become less proliferative and more sensitive to chemotherapy. Our data are consistent with a recent study where BACE inhibition was able to impair melanoma brain metastatic proliferation in vivo (preprint: Kleffman et al, 2019). Indeed, we found that a combined treatment of doxorubicin and NB360 is more effective than doxorubicin alone.…”
Section: Discussionsupporting
confidence: 93%
“…Consistently, we observed that melanoma cells treated with BACE inhibitor become less proliferative and more sensitive to chemotherapy. Our data are consistent with a recent study where BACE inhibition was able to impair melanoma brain metastatic proliferation in vivo (preprint: Kleffman et al, 2019). Indeed, we found that a combined treatment of doxorubicin and NB360 is more effective than doxorubicin alone.…”
Section: Discussionsupporting
confidence: 93%
“…In particular, the BACE1/2 dependent maturation of amyloidogenic proteins such as APP or PMEL, has been shown to affect TME cells behavior and to act both in paracrine and autocrine way driving tumor proliferation and progression [44,48,69]. Importantly, it has also to be noted that β-secretases, besides processing amyloidogenic proteins, have a broad range of substrates; for example, it has been shown that BACE1 can process IL6R, inducing macrophages polarization towards a protumoral phenotype [73].…”
Section: Discussionmentioning
confidence: 99%
“…In details, the authors silenced APP in melanoma cells without affecting melanoma proliferation in vitro but noticed a reduction in brain metastases formation in vivo in a melanoma mouse model. In the same study, they also use a dual BACE1/2 inhibitor to block the production of Aβ in vivo, demonstrating the efficacy of this kind of treatment in reducing the number of brain metastases and tumor burden and suggesting BACE1/2 inhibition as new therapy against melanoma progression [69].…”
Section: Effect Of Bace1/2 On Tmementioning
confidence: 92%
See 2 more Smart Citations